KEMAMPUAN PENYERAPAN ECENG GONDOK TERHADAP AMONIAK DALAM LIMBAH RUMAH SAKIT BERDASARKAN UMUR DAN LAMA KONTAK (STUDI KASUS: RS PANTI WILASA, SEMARANG) - Badrus Zaman; Endro Sutrisno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
Growing of Eichhornia crassipes (Mart), Solms) depend on environmental factors e.g. material organics, sun lighting, water depth, salinity, and pH . However this plant have ability to absorb organic element, organic compound, and other chemical element that can be able to use as biological absorber in waste water treatment.The research is to know the effect of contact time and age of  Eichhornia crassipes (Mart), Solms) toward of ammonia concentration in hospital waste water.The method of this research is Experimental design with One Group Pre Test Post Test Design. The outcome of the research have shown that average ammonia concentration decrease with young plants is 62,17 % at 2 days contact time, 87,1 % at 4 days contact time, and 94,3 % at 6 days contact time. With old plant  ammonia concentration decrease 79,35 % at 2 days contac time, 97,61 at 4 days contact ime, and 98,4 % at 6 days contact time. From the result can be conclude that plant of Eichhornia crassipes (Mart), Solms) had significant ablility to descrease of ammonia concentration in waste water.